The use of intraoperative CT-neuronavigation in Wiltse approach. A technical note - Battistelli, Marco; Valeri, Federico; D’Ercole, Manuela; Izzo, Alessandro; Rapisarda, Alessandro; Polli, Filippo Maria; Montano, Nicola (Frontiers in Surgery, 2024)
IntroductionThe paraspinal approach was first introduced in 1968 and later refined by Leon Wiltse to gain access to the lateral interevertebral foraminal region. However, challenges can arise due to unfamiliarity with this approach, unique patient anatomy, or in case of revision surgery, potentially elevating the risk of complications and/or poor outcome.MethodsHere we report on two cases in which the intraoperative Oarm CT neuronavigation was used during a Wiltse approach. Under general anesthesia, the spinous process near the surgical level is exposed through a midline incision. The patient's reference anchor is then attached to the exposed spinous process. Intraoperative CT is acquired and transferred to the Stealth Station S8 Surgical Navigation System (Medtronic). The Wiltse approach is now performed through a paramedian incision under neuronavigation guidance and perfectly tailored to the patient's unique anatomy.ResultsThe first case was a patient harboring a left lumbar intraextraforaminal schwannoma and the second one was a patient with an extraforaminal lumbar disc herniation at the adjacent level of a previous lumbar instrumentation. We were able to easily identify and remove both the lesions minimizing the surgical approach with no complication and optimal clinical outcome.Discussion and ConclusionOur cases demonstrate the feasibility of application of intraoperative O-arm CT-neuronavigation to the Wiltse approach. In our opinion, this technique helps in minimizing the surgical approach and rapidly identifying the lesion of interest. Further studies are needed to address the effective utility and advantages of intraoperative CT-neuronavigation in this specific surgical scenario.